Ecophysiological Vulnerability to Climate Change in Mexico City’s Urban Forest - Barradas, Victor L.; Esperon-Rodriguez, Manuel (Frontiers in Ecology and Evolution, 2021)
Urban forests play an important role in regulating urban climate while providing multiple environmental services. These forests, however, are threatened by changes in climate, as plants are exposed not only to global climate change but also to urban climate, having an impact on physiological functions. Here, we selected two physiological variables (stomatal conductance and leaf water potential) and four environmental variables (air temperature, photosynthetically active radiation, vapor pressure deficit, and water availability) to compare and evaluate the ecophysiological vulnerability to climate change of 15 dominant tree species from Mexico City’s urban forest. The stomatal conductance response was evaluated using the boundary-line analysis, which allowed us to compare the stomatal response to changes in the environment among species. Our results showed differential species responses to the environmental variables and identified Buddleja cordata and Populus deltoides as the least and most vulnerable species, respectively. Air temperatures above 33 °C and vapor pressure deficit above 3.5 kPa limited the stomatal function of all species. Stomatal conductance was more sensitive to changes in leaf water potential, followed by vapor pressure deficit, indicating that water is a key factor for tree species performance in Mexico City´s urban forest. Our findings can help to optimize species selection considering future climate change by identifying vulnerable and resilient species.